Performance implications of force-vector-specific resistance and plyometric training: a systematic review with meta-analysis - Junge, N.; Jørgensen, T. B.; Nybo, L. (Sports Medicine, 2023)
Background: According to the principle of specific adaptations to imposed demands, training induces specific adaptations that predominantly transfer towards performance tasks of similar physiological and/or biomechanical characteristics. Functional performance improvements secondary to resistance and plyometric training have been hypothesized to be force-vector specific; however, the literature pertaining to this matter appears somewhat equivocal. Objective: The objective of the present systematic review with meta-analysis was to synthesize the available body of literature regarding the performance implications of vertically and horizontally oriented resistance- and plyometric training. Data sources: The review drew from the following sources: PubMed, Web of Science, Scopus, Physiotherapy Evidence Database (PEDro), Cochrane Library, Cumulative Index of Nursing and Allied Health Literature (CINAHL), SPORTDiscus and Google Scholar. Study Eligibility Criteria: To qualify for inclusion, studies had to compare the efficacy of vertically and horizontally oriented resistance and/or plyometric training, with one or multiple outcome measures related to vertical/horizontal jumping, sprinting and/or change of direction speed (CODS). Study Appraisal and Synthesis: For each outcome measure, an inverse-variance random effects model was applied, with between-treatment effects quantified by the standardized mean difference (SMD) and associated 95% confidence- and prediction intervals. Results: Between-treatment effects were of trivial magnitude for vertical jumping (SMD = - 0.04, P = 0.69) and long-distance (= 20 m) sprinting (0.03, P = 0.83), whereas small to moderate effects in favor of horizontal training were observed for horizontal jumping (0.25, P = 0.07), short-distance (= 10 m) sprinting (0.72, P = 0.01) and CODS (0.31, P = 0.06), although only the short-distance sprint outcome reached statistical significance. Conclusions: In conclusion, our meta-analysis reveals a potential superiority of horizontally oriented training for horizontal jumping, short-distance sprinting and CODS, whereas vertically oriented training is equally efficacious for vertical jumping and long-distance sprinting. From an applied perspective, the present analysis provides an advanced basis for weighting of vertical and horizontal force-vector exercises as an integrated component for optimizing sport-specific performances. The present systematic review with meta-analysis was not a priori registered.